Allelopathic potential of essential oils isolated from local plants on common weeds found in Malaysian croplands - Almarie, Ahmed Abdulwahid Ali (School of Bioprocess Engineering, 2017)
Although a considerable amount of work has been carried out and the data generated on the phytotoxic effects of essential oils due to their allelochemical compounds content, to the best of our knowledge, there were limited reports earlier that covered all areas of the essential oils with respect to their effectiveness including mode of action and selectivity. This project was conducted to detect the phytotoxicity of essential oils isolated from eight tropical plant species, which have been explored in limited scale before. The essential oils used in the study are isolated from eight plant species; Cupressus macrocarpa, Melaleuca bracteata, Plectranthus amboinicus Cymbopogon nardus, Pelargonium radula, Baeckea frutescens, Murraya koenigii and Persicaria odorata. The isolated essential oils were evaluated based on their herbicidal activities against the growth of common weed species. The chemical constituents of the essential oils were also identified using GC/MS.